Etiology of end-stage liver cirrhosis impacts hepatic natural killer cell heterogenicity - Maretti-Mira, Ana C.; Salomon, Matthew P.; Hsu, Angela M.; Dara, Lily; Golden-Mason, Lucy (Frontiers in Immunology, 2023)
The natural killer (NK) cell population is a critical component of the innate immune compartment of the liver, and its functions are deeply affected by the surrounding environment. In the late stage of fibrosis, NK cells become dysfunctional, but the influence of disease etiology on NK cell behavior during cirrhosis remains unclear. Using single-cell RNA sequencing (scRNA-seq), we characterized the hepatic NK cells from end-stage cirrhotic livers from subjects with non-alcoholic steatohepatitis (NASH), chronic hepatitis C infection (HCV) and primary sclerosing cholangitis (PSC). Here, we show that although NK cells shared similar dysfunctions, the disease etiology impacts hepatic NK cell heterogeneity. Therapeutical strategies targeting NK cells for the prevention or treatment of fibrosis should consider liver disease etiology in their design.